On The Observance of Grice’s Maxims in Nathan Greno’s Movie Script Tangled - Ida Ayu Made Wulan Sri Dewi (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2022)
This study entitled “On the Observance of Grice’s Maxims in Nathan Greno’s Movie Script Tangled” discussed about the obedience conversational maxims that are found in the conversations that occurred in the movie script. This study aims at finding and analyze the type of Grice’s maxims are applied by the characters in the movie script, along with the meaning of the types are applied by the characters in the movie script Tangled by using Grice (1975) theory. The data were collected by using documentation method and note-taking technique, and were analysed by using a descriptive qualitative method. Based on the result of the data analysis, it showed that the analysis of Grice’s maxims in the Tangled movie script applied all types of the maxims; which are maxim of quantity, quality, relation, and manner.